Case Report: Giant pheochromocytoma complicated by takotsubo syndrome: a case of emergency robot-assisted left adrenalectomy and multidisciplinary management - Miao, Jia; Hu, Xuanhan; Wang, Ting; Liu, Feng; Zhang, Dahong; Wei, Haibin (Frontiers in Oncology, 2025)
Pheochromocytomas are rare neuroendocrine tumors that can cause life-threatening cardiovascular complications due to excessive catecholamine secretion. One such severe manifestation is Takotsubo syndrome (TS), a catecholamine-induced cardiomyopathy that exacerbates hemodynamic instability. The coexistence of a giant pheochromocytoma and TS is extremely rare and presents formidable diagnostic and therapeutic challenges. This case highlights the successful emergency management of this complex condition, demonstrating the feasibility of robotic adrenalectomy in hemodynamically unstable patients. A 45-year-old male presented with dizziness, headache, chest tightness, and palpitations. He was found to have severe hypertension (220/130 mmHg), elevated cardiac biomarkers (BNP 114 pg/mL, cTnI 0.046 ng/mL), and a large left adrenal mass (119 mm × 139 mm × 130 mm). During hospitalization, he experienced alternating hypertensive crises (peak 261/151 mmHg) and profound hypotension (54/32 mmHg), with echocardiography revealing apical ballooning and reduced ejection fraction (45%), consistent with TS. Biochemical analysis showed markedly elevated plasma catecholamine. Given the severe hemodynamic instability despite intensive medical management, an emergency robot-assisted left adrenalectomy was operated. Intraoperatively, significant blood pressure fluctuations occurred (peak 230/100 mmHg), requiring additional vasoactive agent. Pathologic examination confirmed a 14 cm pheochromocytoma. Postoperatively, cardiac function normalized within three months, and catecholamine levels returned to baseline. This case highlights the critical association between pheochromocytoma and TS, underscoring the potential for severe hemodynamic instability in such patients. The successful use of urgent robotic adrenalectomy demonstrates its feasibility and advantages in managing giant pheochromocytoma, even in high-risk patients. This report contributes to the growing evidence supporting minimally invasive techniques in endocrine surgery and emphasizes the necessity of multidisciplinary collaboration in optimizing outcomes for complex pheochromocytoma cases.